Parallelism in embedded microprocessor systems based on clustering - Ruchkin, Vladimir; Romanchuk, Vitaly; Fulin, Vladimir; Kostrov, Boris; Ruchkina, Ekaterina (Mediterranean Conference on Embedded Computing (New Jersey. Online), 2015)
The paper suggests a generic model for compilation and definition of explicit parallelism in embedded computing systems (ECS), based on clustering. It also describes a rule-oriented production model of an expert system for analyzing implicit parallelism that employs a criteria-based fuzzy-set approach, the number of such criteria equal to the number of ECS modules, and also on the microprogram's memory capacity, the system's performance, etc.